Evaluasi Usability Aplikasi Absensi Pegawai Menggunakan System Usability Scale : Studi Kasus di Pemerintah Provinsi Bali - I Made Agus Oka Gunawan; I Gede Teguh Satya Dharma; I Wayan Rizky Wijaya (Program Studi Teknik Informatika - Universitas Komputer Indonesia (UNIKOM), 2026)
This study aims to evaluate the usability of a government employee attendance application using the System Usability Scale (SUS) method. A questionnaire-based survey involving 26 respondents was used in this study. Data were collected through a SUS questionnaire consisting of 10 statements with a five-point Likert scale, then analyzed using the SUS score calculation. This study also mapped SUS items into four usability aspects: effectiveness, efficiency, learnability, and user satisfaction. The results show that the application has a good level of usability and is in the Good category with a Grade B and Acceptable based on a SUS score of 74,62. The results of the measurement of four usability aspects show that the effectiveness aspect obtained a score of 3,13, the learnability aspect obtained a score of 3,03, the efficiency aspect obtained a score of 2,81 and the satisfaction aspect obtained a score of 2,79. These findings indicate that while the application is functionally sound, improvements to the user experience, based on usability, are still needed. The results of this study also provide an empirical basis that can be used as a reference in developing employee attendance applications that are more oriented towards user needs and experience.